2014
DOI: 10.1128/aac.02599-13
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Clinical Trial Comparing the Pharmacokinetics of Standard- and Increased-Dosage Lopinavir-Ritonavir Coformulation Tablets in HIV-Positive Pregnant Women

Abstract: A lopinavir-ritonavir (LPV/r)-based regimen is recommended during pregnancy to reduce the risk of HIV mother-to-child transmission, but the appropriate dose is controversial. We compared the pharmacokinetics of standard and increased LPV/r doses during pregnancy. This randomized, open-label prospective study enrolled 60 pregnant women between gestational weeks 14 and 30. The participants received either the standard dose (400/100 mg twice a day [BID]) or increased dose (600/150 mg BID) of LPV/r tablets during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 35 publications
3
20
0
6
Order By: Relevance
“…A one-compartment model with linear absorption and elimination satisfactorily describes the unbound (unbound model) and total (MFLA model) LPV concentrations in pregnant women. The following observations supported the models developed: the mean half-life value of LPV (5.5 h) and the median CL (5.72 liters/h) were consistent with previous reports (between 5.5 and 5.9 h and between 4.9 to 9 liters/h, respectively) (15)(16)(17)38). The unbound fraction (F u ) was estimated by using the trough concentration; in pregnant women, the median F u was 1.5%.…”
Section: Discussionsupporting
confidence: 77%
“…A one-compartment model with linear absorption and elimination satisfactorily describes the unbound (unbound model) and total (MFLA model) LPV concentrations in pregnant women. The following observations supported the models developed: the mean half-life value of LPV (5.5 h) and the median CL (5.72 liters/h) were consistent with previous reports (between 5.5 and 5.9 h and between 4.9 to 9 liters/h, respectively) (15)(16)(17)38). The unbound fraction (F u ) was estimated by using the trough concentration; in pregnant women, the median F u was 1.5%.…”
Section: Discussionsupporting
confidence: 77%
“…Conflicting reports on the fraction of LPV unbound during pregnancy have been reported. One study demonstrated no change in the fraction of LPV unbound, and four studies reported an increase in the fraction of LPV unbound (16,20,28,47,48). An increase in the fraction unbound may potentially offset at least part of the increase of the LPV clearance during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 summarizes the clinical studies used in this analysis and their dosing and pharmacokinetic sampling schemes. Study 1 was a randomized, open-label prospective study that enrolled 53 HIV-infected pregnant women between 14 and 30 weeks of gestation (20). Subjects were randomized in a 1:1 ratio to receive LPV/r tablets either at 400/100 mg BID or 600/150 mg BID during pregnancy; all participants then received LPV/r at 400/100 mg BID for at least 6 weeks postpartum.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The protective effect of maternal ART on HIV transmission to infants was demonstrated in retrospective and prospective observational studies, randomized clinical trials, systematic reviews and meta-analyses [49,50,47,[51][52][53][54][55][56] . The other benefits of ART during pregnancy are delayed disease progression in the women [50] and reduced risk of HIV transmission to HIV-serodiscordant partners [57].…”
Section: Arv Use During Pregnancymentioning
confidence: 99%